Assessment of the deformability and velocity of healthy and artificially impaired red blood cells in narrow polydimethylsiloxane (PDMS) microchannels - Vilas Boas, Liliana (2020)
Malaria is one of the leading causes of death in underdeveloped regions. Thus, the development of rapid, efficient, and competitive diagnostic techniques is essential. This work reports a study of the deformability and velocity assessment of healthy and artificially impaired red blood cells (RBCs), with the purpose of potentially mimicking malaria effects, in narrow polydimethylsiloxane microchannels. To obtain impaired RBCs, their properties were modified by adding, to the RBCs, different concentrations of glucose, glutaraldehyde, or diamide, in order to increase the cells' rigidity. The effects of the RBCs' artificial stiffening were evaluated by combining image analysis techniques with microchannels with a contraction width of 8 µm, making it possible to measure the cells' deformability and velocity of both healthy and modified RBCs. The results showed that healthy RBCs naturally deform when they cross the contractions and rapidly recover their original shape. In contrast, for the modified samples with high concentration of chemicals, the same did not occur. Additionally, for all the tested modification methods, the results have shown a decrease in the RBCs' deformability and velocity as the cells' rigidity increases, when compared to the behavior of healthy RBCs samples. These results show the ability of the image analysis tools combined with microchannel contractions to obtain crucial information on the pathological blood phenomena in microcirculation. Particularly, it was possible to measure the deformability of the RBCs and their velocity, resulting in a velocity/deformability relation in the microchannel. This correlation shows great potential to relate the RBCs' behavior with the various stages of malaria, helping to establish the development of new diagnostic systems towards point-of-care devices.